Synthesis and Application of Phenyl Nitrone Derivatives as Acidic and Microbial Corrosion Inhibitors - Shijun Chen; Kang Zhao; Gang Chen (Journal of Chemistry)
Nitrone has drawn great attention due to its wide applications as a 1,3-dipole in heterocyclic compounds synthesis and the bioactivities. With the special structure, nitrone can also be used as ligand in inorganic chemistry. Based on the current research, the nitrones are anticipated to be effective inhibitors against acidic and microbial corrosion. The aim of this work is to investigate the inhibitory action of nitrones. In this work, a series of phenyl nitrone derivatives (PN) was synthesized and used as acidic and microbial corrosion inhibitors. The results indicate that several compounds show moderate to high inhibition efficiency (IE) in 3% HCl. Accompanied with HMTA or BOZ, the IEs greatly increase, and the highest efficiency of 98.5% was obtained by using PN4 + BOZ. Investigation of the antibacterial activity against oilfield microorganism shows that the nitrone derivatives can inhibit SRB, IB, and TGB with moderate to high efficiency under 1,000 mg/L, which makes them potential to be used as bifunctional oilfield chemicals.